Myelodysplastic syndrome progress to acute myeloid leukemia: new insights and updates - Zhang, Yucheng; Yan, Lixiang; Fan, Chenyang; Zhao, Bofan; Chen, Meng; Hao, Xiaogang; Zhu, Gengda; Jia, Yanan; Xu, Yajing; Shi, Zhexin (Frontiers in Immunology, 2026)
The progression of myelodysplastic syndromes (MDS) to secondary acute myeloid leukemia (sAML), classified under AML with myelodysplasia-related changes (AML-MRC), is a multi-step process driven by the dynamic interplay between cell-intrinsic genetic events and extrinsic microenvironmental remodeling. In this review, we discuss how these changes foster clonal selection and leukemic transformation. Emerging insights from single-cell technologies are highlighted, revealing the dynamic heterogeneity of MDS stem cells and their niche. Finally, we discussed the clinical implications of these mechanisms, including their impact on risk stratification, therapy failure (particularly after hypomethylating agents), and the development of novel treatment strategies aimed at intercepting progression. Integrating molecular findings with clinical translation is essential for improving outcomes in this high-risk disease continuum.